The Relationship Between Characteristics of Health Workers on Handwashing Behavior - Ossy Wijaya Iriandoko; Djazuly Chalidyanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Based on data from PPI Hospital X in Surabaya there are still nosocomial infections. If the incidence of this infection continues to recur, then the hospital's image will be bad and can cause hospital bed occupational rates to decrease. The purpose of this study was to determine the relationship between the characteristics of health workers (level of knowledge, level of education, age, and length of work) with the level of compliance of health workers doing hand washing at the "X" Hospital in Surabaya. This research is a descriptive correlation study. The sample in this study was 150 health workers working at X Hospital Surabaya, using proportional random sampling stratification technique. Data were collected using a questionnaire instrument. Data analysis using Pearson correlation test. The results revealed a significant relationship between the level of knowledge about handwashing (p = 0.001), an education level (p = 0.004), age (p = 0,000) and years of service (p = 0,000) to the level of compliance of health workers doing hand washing at the "X" Hospital in Surabaya. Surabaya "X" Hospital health workers have a level of compliance with handwashing with a maximum compliance category >75% (76%).